Archaeological exhibition of “The Museum of the History of Yerevan State University”. - Vardanesova, Tatyana (History and Culture, 2025)
“Museum of History of Yerevan State University named after. Prof. L. Gharibjanyan" reflects the history of one of the largest universities in Armenia - Yerevan State University, which celebrated its centenary in 2019. In 2009, for the 90th anniversary of YSU, the museum was rebuilt, and the exhibition was recreated based on extensive exhibition and museum funds. During the creation of the new exhibition, in the museum's funds discovered some boxes with archaeological material from excavations on the territory of Armenia. These artifacts are the result of past archaeological expeditions of the Department of Archeology of YSU, which collected over many years. These artifacts were without documentation and never exhibited. The collection required restoration and description. It was decided to present part of the archaeological material in the form of a separate exhibition of artifacts in frames of new museum. It should organically be included in the overall concept of the museum. In the process of working on this archaeological exhibition, some item were restored in the “Archaeological Laboratory of the Armenian Studies Institute of YSU”, and some remained in the funds. In 2023, the joint work of the «Archaeological laboratory” and the museum resumed. For the restoration, study and attribution of some archaeological material, ceramics from the early Bronze and middle Ages were transported from the museum’s fund to the “Archaeological Laboratory”. The article is devoted to the analysis of the work on restoration and attribution of this material.
Keywords: Museum of Yerevan State University; archaeological material; ceramics; exhibition; early bronze; medieval ceramics